Influence of APOE Genotype on Mortality and Cognitive Impairment - Robinson, Andrew C. (J Alzheimers Dis Rep, 2020)
While many studies have examined the associations between APOE genotype and mortality, findings have often been conflicting and it remains unclear whether APOE genotype affects longevity. Using selected individuals from the Manchester arm of the Brains for Dementia Research programme and University of Manchester Longitudinal Study of Cognition in Normal Healthy Old Age, we investigated relationships between APOE genotype and age at death in both cognitively normal and cognitively impaired individuals. Results indicated that carrying the APOE ɛ4 allele led to a reduced chance in an individual reaching 80+ years and remaining cognitively healthy. Conversely, APOE ɛ2 carriers tended to live longer and remain cognitively normal. These findings add to the evidence that APOE genotype influences longevity, especially in cognitively impaired individuals who carry the APOE ɛ4 allele.